الأحاديث التي أعلها النسائي بالتفرد في السنن الكبرى دراسة لبعض النماذج - الأطرش مسعودة (University of Eloued جامعة الوادي, 2024)
"هذه الدراسة بعنوان ""الأحاديث التي أعلها الإمام النسائي بالتفرّد في السنن الكبرى""، وتتكون من مقدمة وثلاثة مباحث وتحت كل مبحث مطالب وخاتمة. حيث تضمنت الدراسة مبحث تمهيدي تناولت فيه ترجمة موجزة للإمام النسائي والتعريف بكتابه السنن الكبرى، والمبحث الثاني يتضمن الدراسة النظرية وقسمته إلى ثلاثة مطالب، المطلب الأول: عرّفت فيه العلة وأقسامها والمؤلفات فيها، والثاني: ذكرت فيه تعريف التفرّد وأقسامه والمؤلفات فيه، والثالث: عرّفت فيه الغريب مع ذكر أقسامه باختصار، ثم تطرقت إلى الدراسة التطبيقية، وهي لأحاديث التي أعلها النسائي بالتفرّد في السنن الكبرى، ودرست ثمانية نماذج، كل نموذج في مطلب، أورد رواية النسائي التي نص على تعليلها ثم أقوم بشرح نص النسائي في تعليل الحديث، وأذكر تخريج الرواية المعلولة من مصادر السنة، وقمت بترجمة للرواة الذين نص النسائي على تفردهم وعمن رووا، وأحياناً أورد ترجمة لبعض الرواة غيرهم، ثم أذكر تخريج الرواية الصحيحة وأنقل كلام النقاد في الأحاديث التي أعلها الإمام النسائي، وأذكر خلاصة عقب كل حديث، ثم ختمت الرسالة بما توصلت إليه من نتائج وتوصيات. This study is entitled “Hadiths that Imam al-Nasa’i declared to be unique in Sunan al-Kubra,” and it consists of an introduction, three chapters, and under each chapter are demands and a conclusion. The study included an introductory section in which I dealt with a brief biography of Imam al-Nasa'i and an introduction to his book al-Sunan al-Kubra. The second section includes the theoretical study and is divided into three sections. The first section: I defined the defect and its sections and the books on it. The second section: I mentioned the definition of singularity and its sections and the books on it. The third section: I defined the strange and mentioned its sections briefly. Then I turned to the applied study, which is for the hadiths that al-Nasa'i declared to be unique in al-Sunan al-Kubra. I studied eight models, each model in a section. I cited al-Nasa'i's narration that he stated to be unique, then I explain al-Nasa'i's text in explaining the hadith, and I mention the graduation of the defective narration from the sources of the Sunnah. I provided a translation of the narrators that al-Nasa'i stated to be unique and from whom they narrated. Sometimes I provide a translation of some narrators other than them. Then I mention the graduation of the correct narration and I convey the critics' words on the hadiths that Imam al-Nasa'i declared to be unique. I mention a summary after each hadith, then I conclude the thesis with the results and recommendations I reached.
Keywords: الحديث، العلة، النسائي، السنن الكبرى، التفرّد; Hadith; Illness; Al-Nisa’i; Sunan Al-Kubra; Uniqueness